The Complete Sequences and Ecological Roles of Two IncP-1β Plasmids, pHB44 and pBS64, Isolated from the Mycosphere of Laccaria proxima - Zhang, Miaozhi; Brons, Jolanda K.; van Elsas, Jan Dirk (Frontiers in Microbiology, 2016)
Two novel plasmids, coined pHB44 and pBS64, were recently found in Variovorax paradoxus strains HB44 and BS64 isolated from the mycosphere of Laccaria proxima, on two different sampling occasions. We here describe the full sequences of pHB44 and pBS64 and establish their evolutionary placement and ecological function. Both plasmids, unique for mycospheric V. paradoxus, were around 58 kb in size. They possessed, in a very similar fashion, three main plasmid backbone regions, which were predicted to be involved in plasmid replication, central control of maintenance and conjugational transfer. Phylogenetic inference on the basis of seven selected and concatenated plasmid backbone genes provided solid evidence for the placement of the two plasmids in the IncP-1β1 group, with the recently isolated IncP-1β1 plasmid pMBUI8 as the closest relative. A comparative analysis of the sequences present in each of the insertional hot spots I to III across plasmids pHB44, pBS64 and pMBUI8 revealed the insertions found in plasmids pHB44 and pBS64 to be different from those of pMBUI8. Whereas, in the former two plasmids, hot spots I and III were devoid of any major inserts, their hot spot II regions contained inserts of 15,400 (pHB44) and 16,697 kb (pBS64), against about 11 kb for pMBUI8. Interestingly, these regions were highly similar across plasmids pHB44 and pBS64, and differed from that of pMBUI8. Closer inspection revealed the insert in the former plasmids to contain, next to transposases, an ‘mmf’ gene cassette previously reported to encode metal ‘responsiveness’ in the PromA plasmid pMOL98. Whereas the plasmid pHB44 hot spot II contained the canonical mmf sequence, that in pBS64 contained, in addition, two genes for similar transposases flanking the mmfC2 gene. In vitro experiments on the growth and survival of strains with or without plasmid pHB44 revealed this plasmid to be involved in the binding and import of Fe3+ as well as V3+ ions into the host cells, thus yielding a growth advantage under ‘metal ion-limiting’ conditions. In addition, pHB44 was found to confer a bacitracin resistance phenotype to its host strain HB44. The metal import and bacitracin resistance traits were, on theoretical grounds, attributed to